2021
DOI: 10.1161/hypertensionaha.120.16676
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intensive Blood Pressure Control on Aortic Stiffness in the SPRINT-HEART

Abstract: In a subgroup of 337 participants (mean age 64±9 years; 45% women) from the SPRINT (Systolic Blood Pressure Intervention Trial), where participants were randomly assigned to intensive treatment (target systolic blood pressure <120 mm Hg) versus standard treatment (<140 mm Hg), we examined the effect of intensive blood pressure lowering on indexes of aortic stiffness. Carotid-femoral pulse wave velocity, a validated global measure of aortic stiffness, was measured by echo-guided Doppler at baseline and 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…In this study, we found that the follow-up baPWV increased by 3.48% in the intensive group and 5.09% in the standard group. Accordingly, the SPRINT-Heart 13 study showed that PWV increased by 8.2% in the standard group (SBP target ≤140 mm Hg) and did not significantly increase in the intensive group (SBP target ≤120 mm Hg). It is not clear whether the effect of SBP lowering treatment on arterial stiffness is the result of SBP reduction or the effect of antihypertensive drugs on arteries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found that the follow-up baPWV increased by 3.48% in the intensive group and 5.09% in the standard group. Accordingly, the SPRINT-Heart 13 study showed that PWV increased by 8.2% in the standard group (SBP target ≤140 mm Hg) and did not significantly increase in the intensive group (SBP target ≤120 mm Hg). It is not clear whether the effect of SBP lowering treatment on arterial stiffness is the result of SBP reduction or the effect of antihypertensive drugs on arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Both STEP trial (Strategy of Blood Pressure Intervention in the Elderly Hypertensive Patients) 11 and SPRINT (Systolic Blood Pressure Intervention Trial) 12 found that intensive SBP control significantly reduced the risk of CVD. Furthermore, the SPRINT-Heart trial 13 demonstrated that intensive treatment of SBP significantly attenuated the progression of arterial stiffening in patients with hypertension. However, whether intensive SBP control can alter or counteract the effect of arterial stiffening on SBP is unclear.…”
mentioning
confidence: 99%
“…Given that AS is common in the elderly population [ 28 ], the balance of risks and benefits from intensive SBP treatment should be carefully evaluated according to the AS status of these patients. Previous analyses of the SPRINT trial have shown that intensive treatment significantly attenuates increases in the cfPWV and aortic elastance index, suggesting that attenuating AS progression might be one of the mechanisms underlying the cardiovascular benefit obtained from intensive SBP intervention [ 29 , 30 ]. However, previous researchers did not investigate the influence of the baseline PWV status on the effects of intensive SBP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial stiffness is an early marker of cardiovascular (CV) risk and has been shown to predict CV events independently of traditional risk factors [6,7]. In addition, reduction in arterial stiffness may be associated with improved CV outcome [8,9]. The gold standard for assessing arterial stiffness is carotidfemoral pulse wave velocity (cfPWV) [10].…”
Section: Introductionmentioning
confidence: 99%